Mobile commerce adoption: A value perspective from a developing country - Ben Abdennebi, Hela (Journal of Telecommunications and the Digital Economy, 2025)
This study explores the factors affecting mobile commerce adoption in Tunisia using the Stimulus-Organism-Response (S-O-R) framework. It examines how accessibility, convenience, ubiquity, and design aesthetics impact perceived value, which, in turn, influences adoption behaviour. Based on data from 613 respondents and analysed through structural equation modelling (PLS-SEM), the study finds that perceived emotional and quality value significantly drive adoption intentions, with emotional value being more influential. Design aesthetics are found to play a key role in shaping perceived value, boosting perceived quality value by 34%, emotional value and social value by 30%, and price value by 33%. Convenience enhances perceived price value, while both accessibility and convenience positively impact perceived quality and emotional value. This study will be helpful to researchers in further understanding the S-O-R framework in the context of mobile commerce adoption, as well as to mobile commerce practitioners in understanding the environmental stimuli that impact the consumer’s perceived value of mobile commerce, leading them to adopt it. Theoretical and managerial implications of our results are discussed.